PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL)PADA PEMBELAJARAN TEMATIK TERPADU SISWA KELAS IV - susanti susanti (Universitas Bengkulu, 2022)
This study discusses the Development of Student Worksheets Based on Contextual Teaching And Learning (CTL) in Integrated Thematic Learning for Class IV Students. The objectives to be achieved are to find out and describe the feasibility and responses of teachers and students regarding Contextual Teaching and Learning-Based Student Worksheets. This research is research and development. The research development model used modifies the 4D model. The object of this development research is a product of teaching materials in the form of thematic LKPD based on Contextual Teaching and Learning. While the subjects in this study were experts and teachers of elementary school 89 Bengkulu City. The instruments in this study include validation sheets and questionnaires for teacher and student responses. The results of expert validation between stage I and stage II showed a significant increase. Based on expert validation assessments and teacher responses and student responses, LKPD using the developed CTL model is very good to use. The CTL model is able to provide learning that is in accordance with the characteristics of elementary school children who are in the concrete operational period. In addition, the CTL model is in accordance with thematic learning with its ability to present students' world of learning in a holistic, meaningful, authentic, and active way for students.